2006
DOI: 10.1017/cbo9780511546112
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Solutions in Elastodynamics

Abstract: This 2006 work is a compilation of fundamental solutions (or Green's functions) for classical or canonical problems in elastodynamics presented with a common format and notation. These formulas describe the displacements and stresses elicited by dynamic sources in solid elastic media like full spaces, half-spaces, strata and plates in both two and three dimensions, using the three major coordinate systems (Cartesian, cylindrical and spherical), and also for transient and harmonic motions. Such formulas are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
173
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(176 citation statements)
references
References 0 publications
2
173
0
1
Order By: Relevance
“…as also given by Kausel (2006). Zipora Alterman (1925-1974) and Dan Loewenthal (1943-2000 -henceforth referred to as A&L for short-were both Professors of Geophysics at Tel Aviv University, and both passed away at the relatively young ages of 49 and 57 years, respectively.…”
Section: Garvin's Classical Problemmentioning
confidence: 90%
See 1 more Smart Citation
“…as also given by Kausel (2006). Zipora Alterman (1925-1974) and Dan Loewenthal (1943-2000 -henceforth referred to as A&L for short-were both Professors of Geophysics at Tel Aviv University, and both passed away at the relatively young ages of 49 and 57 years, respectively.…”
Section: Garvin's Classical Problemmentioning
confidence: 90%
“…This powerful strategy has been widely used and is commonly referred to as the Cagniard-de Hoop method, in honor of their inventors (De Hoop, 1960). After this is done, the response functions at the surface are found to be given by the following expressions (see Kausel, 2006, but appropriately modified to account for the different sign convention employed herein for the vertical direction):…”
Section: Garvin's Classical Problemmentioning
confidence: 99%
“…axis) to a harmonic force in some fixed radial direction, say the horizontal, which causes the cylinder to oscillate in that direction, and the ratio of the applied force to the observed oscillation is the lateral dynamic stiffness or impedance of the cylinder. This is conceptually similar to the problem of a semi-cylindrical foundation at the surface of an elastic half-space undergoing oscillations transverse to the free surface, but the latter is more It can be shown (Kausel, 2006) that the cylindrical displacement components at any arbitrary point and the stresses acting on cylindrical surfaces are of the form…”
Section: Counter-example 2: Layered Rod (1-d)mentioning
confidence: 99%
“…It can be shown that the torsional response of the sphere is governed by the following equations in spherical coordinates, e.g. see Kausel, 2006:…”
Section: K F H H F H H H H F H F H H H H H (19)mentioning
confidence: 99%
“…From the different available methods based on the wavenumber/frequency domain approach, a hybrid formulation of the Thin Layer Method (TLM) [12,13] and the Direct Stiffness Matrix Method (DSMM) [12,14] is used for the calculation of the response field in the soil. In both these methods, which are similar to the finite element method, element stiffness matrices are used to express the relation between displacements and stresses at the soil element boundaries.…”
Section: Semi-analytical Approachmentioning
confidence: 99%